2016
DOI: 10.1002/cce2.20
|View full text |Cite
|
Sign up to set email alerts
|

Update on current TAVI technology, indications, screening, and outcomes

Abstract: Transcatheter aortic valve replacement (TAVI) is an established treatment for inoperable patients or patients at high surgical risk with severe aortic stenosis. Herein, we illustrate the key design features of the main new generation devices that are entering contemporary clinical practice, the labeled and off-labeled indications, the basic principles of screening process, and the clinical outcomes of the TAVI procedure.Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/ 4193543/Activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…16 In concordance with the clinical and anatomical considerations discussed in Table 1, the recent EACTS and American Heart Association (AHA) guidelines agree that the main recommendations for TAVI in patients with severe aortic stenosis must have the T A B L E 1 Considerations made for the decision between TAVI and SAVR in patients with severe aortic stenosis (based on the 2017 European Association for Cardio-thoracic Surgery guidelines on the management of valvular heart disease) following two indications: a life expectancy greater than 1 year and representing a high surgical risk. 17 However, in the presence of trials encouraging surgical intervention for severe aortic valve disease with good long-term results, Akin et al 18 suggested an algorithm to determine the most suitable treatment intervention for patients with severe aortic stenosis, Figure 1.…”
Section: Indications and Patient Selection For Tavimentioning
confidence: 99%
“…16 In concordance with the clinical and anatomical considerations discussed in Table 1, the recent EACTS and American Heart Association (AHA) guidelines agree that the main recommendations for TAVI in patients with severe aortic stenosis must have the T A B L E 1 Considerations made for the decision between TAVI and SAVR in patients with severe aortic stenosis (based on the 2017 European Association for Cardio-thoracic Surgery guidelines on the management of valvular heart disease) following two indications: a life expectancy greater than 1 year and representing a high surgical risk. 17 However, in the presence of trials encouraging surgical intervention for severe aortic valve disease with good long-term results, Akin et al 18 suggested an algorithm to determine the most suitable treatment intervention for patients with severe aortic stenosis, Figure 1.…”
Section: Indications and Patient Selection For Tavimentioning
confidence: 99%
“…The Lotus prosthesis from Boston Scientific also consists of a nitinol frame with a round shape when expanded and valve leaflets of bovine pericardium. A flexible polyurethane/polycarbonate seal around the lower half of the stent frame (adaptive seal) prevents paravalvular leaks [9]. In contrast to the other two prostheses, the Lotus valve prosthesis is expanded mechanically via three arms and not automatically or via balloon catheter.…”
Section: Lotus Prosthesismentioning
confidence: 99%
“…This allows relatively controlled insertion of the valve and also the option of retrieving and repositioning the valve even after complete expansion. An additional radiopaque tantalum marker in the center of the stent frame facilitates positioning of the valve [9]. During expansion of the stent, the stent frame shortens and the marker moves in the direction of the annulus until it reaches the correct position at the level of the sinus of Valsalva, approx.…”
Section: Lotus Prosthesismentioning
confidence: 99%
See 1 more Smart Citation